Constitucional o inconstitucional: Disolución del Congreso - Mendívil, José (2019)
In this article I refer to the questionable points of the order for the admissibility of the competence filed before the Constitutional Court by the President of the Permanent Commission of the Congress of the Republic, which questions the dissolution of the Congress of the Republic, such as the arguments of the courts regarding Said Auto Admissive. Likewise, I refer to what is stated in Order by the Constitutional Court in response to the motion for replacement or clarification of the Order admissible raised by the Permanent Commission; also the Ombudsman's arguments regarding the dissolution of the Congress of the Republic, contained in the Ombudsman's Report on the political crisis, a matter of trust and dissolution of the congress. I show the limits of the Peruvian constitutional law that regarding the dissolution of the Congress of the Republic rejects the precautionary measure of the Permanent Commission against Supreme Decree No. 165-2019-PCM, precautionary that was denied by simple majority and that it proposed to be temporarily suspended the closing of the Congress of the Republic made by decision of the President of the Republic. I question the separation that the Court makes of the political and the constitutional, which is debatable if one takes into account that the Venice Commission regarding the issue of whether it is constitutional to link the constitutional reform to a matter of trust as the government has done That being said, although what is affirmed by this has no binding value, that in comparative law, linking constitutional amendments to a matter of trust is unusual. I do not qualify the act of dissolution of the Congress, because I consider that said act as singular deserves a more abundant treatment from political theory and constitutional law with the purpose of giving analysis tools to the need to reform our political or power regime.